An Interview Study on Professor Chen Zhi’s Pedagogical Approach to Classical Guitar Education in China (Journal of Interdisciplinary Insights, 2025)
This study investigates the pedagogical philosophy and contributions of Professor Chen Zhi, a pioneering figure in the development of classical guitar education in China. Drawing upon a semi-structured interview with Professor Chen, supplemented by archival materials and secondary sources, the research explores how he integrated Chinese cultural traditions with innovative teaching methods to professionalize guitar pedagogy. Central to Chen’s approach is his adaptation of the Four Diagnostic Methods from traditional Chinese medicine：Wàng (Observation), Wén (Listening), Wèn (Inquiry), and Qiè (Palpation). Through this method, Chen emphasized personalized teaching, rigorous technical training, and holistic student development. The findings highlight how his philosophy of gradual progression, attention to detail, and motivational strategies not only elevated student performance but also reshaped the institutional status of the guitar in China. He established the country’s first formal guitar school and founding the program at the Central Conservatory of Music, and provided structural foundations for the professionalization of the instrument. This study concludes that Chen’s integration of tradition and innovation created a unique model of pedagogy that bridges cultural heritage with modern performance standards. It further suggests that his approach offers valuable insights for contemporary music education, particularly in contexts seeking to balance local identity with global engagement.
Keywords: Classical guitar pedagogy; Chen Zhi; Chinese music education; Four Diagnostic Methods; tradition and innovation; individualized instruction